Pentingnya Keterampilan Berbicara pada Siswa Sekolah Dasar di Lingkungan Rumah - Triyanti, Ni Komang Soni; Septarini, Ni Luh Putu Diah; Setiawati, Ni Komang Martiwi; Apriana, I Nyoman Arya; Dewi, Ni Made Tiara Santika; Werang, Basilius Redan (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
This study aims to analyze the importance of using speaking skills in the home environment in elementary school students. Speaking skills are an important aspect of a person's communication skills. In the home environment, these skills develop through daily interactions with family members, which provides opportunities for children to practice speaking without pressure. This research method is qualitative descriptive by using purposive sampling to select research subjects. The techniques used in collecting data are observation, documentation, and interviews involving teachers, parents, and grade IV students of SD Negeri 3 Pedungan. The data validation technique uses triangulation techniques. The results of the study show that the development of speaking skills in the home environment brings various benefits, both academically and socially for students. This includes increased self-confidence, better academic and social readiness, and improved critical thinking skills. The importance of developing speaking skills in the home environment not only affects students' verbal abilities, but also enriches the social, emotional, and cognitive aspects of their development.